Environmental disclosure quality of ISO14001 companies and differences in companies' characteristics - Mohd Said, Ridzwana; Liew, Lai Teng; Senik, Rosmila; Yusri, Yusniyati (Academic Inspired Network, 2020)
Quality of environmental disclosure is important as it indicates the usefulness, comprehensibility, relevance, reliability and comparability to users of information. With the emergence of digital technology, Internet is used as a new medium for environmental disclosure. However, quality of such disclosure is still debatable. ISO14001 certification is an indicator to determine the quality of environmental information. Thus, this study examined the difference in quality of web-based environmental disclosure between ISO14001 and nonISO14001 certified company in Malaysia and the differences in environmental information quality based on company profitability, leverage and auditor’s type. Content analysis was adopted, and Mann-Whitney U test was used to analyse the differences in disclosure quality. The analysis revealed that there is a different in disclosure quality between ISO14001 and nonISO14001 certified company, while no differences in disclosure quality between high and low profitability companies, high and low leverage companies and companies audited by big four and non-big four auditors.